2020
DOI: 10.1111/anec.12805
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiograhic characteristics in patients with coronavirus infection: A single‐center observational study

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 21 publications
2
40
0
2
Order By: Relevance
“…For external validation, patients admitted to the Wuhan Asia General Hospital 38 , Wuhan, China, between 10 February and 10 March 2020, were included. Diagnosis of COVID-19 was based on positive PCR test and ground glass shadows in the lungs on computed tomography scan, with follow-up 2 weeks post-discharge.…”
Section: Methodsmentioning
confidence: 99%
“…For external validation, patients admitted to the Wuhan Asia General Hospital 38 , Wuhan, China, between 10 February and 10 March 2020, were included. Diagnosis of COVID-19 was based on positive PCR test and ground glass shadows in the lungs on computed tomography scan, with follow-up 2 weeks post-discharge.…”
Section: Methodsmentioning
confidence: 99%
“…COVID-19 infection associated with myocardial injury may demonstrate ST segment deviations (elevation or depression), T wave inversion, and pathologic Q waves [ [3] , [4] , [5] , 19 , 20 , 69 ]. One study found ST segment and T wave changes to be the most common abnormality in patients requiring ICU admission, occurring in 40% of patients [ 70 ]. Another investigation noted that nonspecific repolarization changes including ST segment and T wave abnormalities were encountered in 41% of patients; reportedly, these findings resulted from myocardial injury and are associated with poor outcomes, including increased need for ICU admission, more frequent mechanical ventilatory support, and increased mortality [ 32 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, electrocardiography (ECG) may be useful to discern acute myocardial injury or rhythm alterations in COVID-19 patients. ECG characteristics in COVID-19 pneumonia have been already described in previous studies, but their relations to outcomes are still debated [ 5 7 ]. The aim of the present study was, indeed, to explore ECG abnormalities at admission in all-comer COVID-19 patients admitted to the Emergency Department of Modena University Hospital.…”
Section: Introductionmentioning
confidence: 99%